2021
DOI: 10.1002/ajoc.202100473
|View full text |Cite
|
Sign up to set email alerts
|

Radical Cation [4+2] Cycloaddition of Non‐Conjugated Tetrasubstituted Alkenes by an FeCl3/AgSbF6 Co‐Initiator

Abstract: Radical cation [4+2] cycloaddition is an alternative strategy for constructing various six‐membered rings that cannot be easily accessed by thermal [4+2] cycloaddition. Here, we developed an FeCl3/AgSbF6 co‐initiator to promote radical cation [4+2] cycloaddition of non‐conjugated tetrasubstituted alkenes with 2,3‐dimethyl‐1,3‐butadiene. In the presence of 10 mol% of FeCl3 and 30 mol% of AgSbF6, the reaction proceeded smoothly in MeCN to provide the cycloadducts from tetrasubstituted alkenes having an electron‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…14 In addition to the electrocatalytic system, Ishihara and co-workers developed a FeCl 3 /AgSbF 6 co-catalysis method to promote radical cationic (4 + 2) cycloaddition by employing tetrasubstituted alkenes and 2,3-dimethyl-1,3-butadiene (Scheme 6b). 15 One year later, the group of You and Kang disclosed an interesting green light-driven radical cationic (4 + 2) cycloaddition of nucleophilic dienes and terminal chain alkenes by using Fe III (btz) 3 as a photocatalyst (Scheme 6c). 16 It was found that the ligand-to-metal charge-transfer transition state formed in this process had a high excited-state reduction potential for the selective oxidation of terminal styrene derivatives.…”
Section: Alkenyl Radical Cations or Alkenyl Radicalsmentioning
confidence: 99%
“…14 In addition to the electrocatalytic system, Ishihara and co-workers developed a FeCl 3 /AgSbF 6 co-catalysis method to promote radical cationic (4 + 2) cycloaddition by employing tetrasubstituted alkenes and 2,3-dimethyl-1,3-butadiene (Scheme 6b). 15 One year later, the group of You and Kang disclosed an interesting green light-driven radical cationic (4 + 2) cycloaddition of nucleophilic dienes and terminal chain alkenes by using Fe III (btz) 3 as a photocatalyst (Scheme 6c). 16 It was found that the ligand-to-metal charge-transfer transition state formed in this process had a high excited-state reduction potential for the selective oxidation of terminal styrene derivatives.…”
Section: Alkenyl Radical Cations or Alkenyl Radicalsmentioning
confidence: 99%